Innovating the outreach of comprehensive cancer centers - Christian H. Brandts (Molecular Oncology, 2019)
In many countries, a majority of cancer patients are not treated at comprehensive cancer centers. Even for those that are, parts of the treatment or follow‐up may be carried out in local community hospitals or in private practices. How to assure quality in cancer care and create innovation? How to integrate decentralized versus centralized patient care, education, and cancer research? Outlined here is a 360° view of outreach to include all stakeholders—most importantly patients and their families, patient advocacy groups, healthcare providers, health insurers, and policymakers.